Free radical reactions in atherosclerosis; An EPR spectrometry study. Issue 2 (2006) - Taiwo Taiwo, F. A. F. A.; Powers Powers, H. J. H. J.; Nakano Nakano, E. E.; Griffiths Griffiths, H. R. H. R.; Nugent Nugent, D. F. D. F.
Abstract : The copper catalysed oxidation of homocysteine has been studied by electron paramagnetic resonance (EPR) spectroscopy and spin trapping techniques to determine the nature of free radical species formed under varying experimental conditions. Three radicals; thiyl, alkyl and hydroxyl were detected with hydroxyl being predominant. A reaction mechanism is proposed involving Fenton chemistry. Inclusion of catalase to test for intermediate generation of hydrogen peroxide showed a marked reduction in amount of hydroxyl radical generated. In contrast, the addition of superoxide dismutase showed no significant effect on the level of hydroxyl radical formed. Enhanced radical formation was observed at higher levels of oxygen, an effect which has consequences for differential oxygen levels in arterial and venous systems. Implications are drawn for a higher incidence of atherosclerotic plaque formation in arteries versus veins.